Criminalised, victimised or other? A reflexive engagement with Queer Criminology utilising a relational pedagogical approach - Wrigley, Liam; Koumentaki, Evangelia (Frontiers in Sociology, 2024)
Queer Criminology is a newfound area of exploration within the discipline of Criminology, which is uniquely positioned to deal with issues regarding crime and victimisation concerning those from the LGBTQIA+ community and gender diverse/minoritized groups. The field of 'Queer Criminology' has become vast and expanding, having explored issues of interpersonal, structural and systematic inequality concerning those from the community and beyond. To this end, narratives of victimisation, trauma and injustice have dominated (and limited) understandings of Queer Criminology. Moreover, limited thinking has been attributed within the Scholarship of Teaching and Learning (SOTL), which seeks to understand LGBTQIA+ individuals and groups -beyond binarized thinking of victimhood or criminalised. In this article, we offer the perspectives of two higher education professionals teaching Queer Criminology in a 'flipped' classroom environment, which positions the learner as expert within the subject matter and utilises a relational pedagogy lens to do so (Bovil, 2020). We discuss the use of our reflexive practice, as both Feminist Decolonial and Queer Criminologists. The article touches upon trauma informed approaches to teaching Queer Criminology. We offer several steps in building a coalition of learning, which can unpick the potential policy, theory, and practical tensions of teaching Queer Criminological Scholarship.